Molecular mechanisms of cholesterol or homocysteine effect in the development of atherosclerosis: Role of vitamin E - (:unkn) unknown (WILEY, 2003)
The development of atherosclerosis is a multifactorial process in which both elevated plasma cholesterol levels and proliferation of smooth muscle cells play a central role. Numerous studies have suggested the involvement of oxidative processes in the pathogenesis of atherosclerosis and especially of oxidized low density lipoprotein. Some epidemiological studies have shown an association between high dietary intake and high serum concentrations of vitamin E and lower rates of ischemic heart disease. Cell culture studies have shown that alpha-tocopherol brings about inhibition of smooth muscle cell proliferation. This takes place via inhibition of protein kinase C activity. alpha-Tocopherol also inhibits low density lipoprotein induced smooth muscle cell proliferation and protein kinase C activity. The following animal studies showed that vitamin E protects development of cholesterol induced atherosclerosis by inhibiting protein kinase C activity in smooth muscle cells in vivo. Elevated plasma. levels of homocysteine have been identified as an important and independent risk factor for cerebral, coronary and peripheral atherosclerosis. However the mechanisms by which homocysteine promotes atherosclerotic plaque formation are not clearly defined. Earlier reports have been suggested that homocysteine exert its effect via H2O2 produced during its metabolism. To evaluate the contribution of homocysteine in the pathogenesis of vascular diseases, we examined whether,the homocysteine effect on vascular smooth muscle cell growth is mediated by H2O2. We show that homocysteine induces DNA synthesis and proliferation of vascular smooth muscle cells in the presence of peroxide scavenging enzyme, catalase. Our data suggest that homocysteine induces smooth muscle cell growth through the activation of an H2O2 independent pathway and accelerate the progression of atherosclerosis. The results indicate a cellular mechanism for the atherogenicity of cholesterol or homocysteine and protective role of vitamin E in the development of atherosclerosis.
Keywords: cholesterol; homocysteine; vitamin E; atherosclerosis; SMOOTH-MUSCLE-CELLS; PROTEIN-KINASE-C; CORONARY-HEART-DISEASE; ALPHA-TOCOPHEROL; CARDIOVASCULAR RISK; PLASMA HOMOCYSTEINE; E CONSUMPTION; PROLIFERATION; RABBITS; INJURY